2022
DOI: 10.1200/jco.21.01604
|View full text |Cite|
|
Sign up to set email alerts
|

Overall Survival Results From the POLO Trial: A Phase III Study of Active Maintenance Olaparib Versus Placebo for Germline BRCA-Mutated Metastatic Pancreatic Cancer

Abstract: PURPOSE The phase III POLO study demonstrated significant progression-free survival (PFS) benefit for active olaparib maintenance therapy versus placebo for patients with metastatic pancreatic adenocarcinoma and a germline BRCA mutation. Here, we report the final analysis of overall survival (OS) and other secondary end points. PATIENTS AND METHODS Patients with a deleterious or suspected deleterious germline BRCA mutation whose disease had not progressed after ≥ 16 weeks of first-line platinum-based chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 41 publications
1
61
0
1
Order By: Relevance
“…Although mutations of BRCA1/2 in PDAC are associated with increased survival due to a higher susceptibility to platinum-based chemotherapy ( 45 , 46 ), this observation could not be confirmed for HROP68, harboring a BRCA1 mutation. While BRCA -mutated ovarian cancers respond well to the inhibitors of the poly-ADP ribose (PARPi), the PARPi olaparib improved progression-free survival in metastatic PDAC patients with a germline BRCA mutation but failed to improve overall survival ( 47 , 48 ). In our study, olaparib had an inhibitory effect on HROP68Tu2 cells in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Although mutations of BRCA1/2 in PDAC are associated with increased survival due to a higher susceptibility to platinum-based chemotherapy ( 45 , 46 ), this observation could not be confirmed for HROP68, harboring a BRCA1 mutation. While BRCA -mutated ovarian cancers respond well to the inhibitors of the poly-ADP ribose (PARPi), the PARPi olaparib improved progression-free survival in metastatic PDAC patients with a germline BRCA mutation but failed to improve overall survival ( 47 , 48 ). In our study, olaparib had an inhibitory effect on HROP68Tu2 cells in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The use of PARPi in PACC patients with germline BRCA1 or BRCA2 PV/LPV is anecdotal[ 2 , 23 , 26 ]. Furthermore, the updated analysis of the POLO trial showed a lack of OS benefit and quality of life improvement in their Olaparib-treated patients compared to the placebo arm[ 39 ]. Despite the aforementioned, we believe that metastatic PACC patients with confirmed HRD phenotype and demonstrated strictly defined platinum sensitivity that involved exceptional response after 16 wk of chemotherapy should be considered for the benefit of PARPi, as the case described.…”
Section: Discussionmentioning
confidence: 99%
“…This insight led to the design of the POLO trial, where maintenance olaparib versus placebo was studied in patients with PDAC with deleterious germline BRCA1 or BRCA2 mutations who had no evidence of disease progression following at least 16 weeks of platinum-based chemotherapy. The trial met its primary endpoint of improving PFS (7.4 months versus 3.8 months, olaparib versus placebo), but did not demonstrate a statistically significant improvement in OS [ 43 , 44 ]. On the basis of the POLO trial, the FDA approved maintenance olaparib in PDAC patients with germline BRCA mutations.…”
Section: Biomarker-driven Therapymentioning
confidence: 99%